Efficacy of Conventional Versus Accelerated Corneal Cross-linking in Pediatric Keratoconus: Two-Year Outcomes - (:unkn) unknown (SLACK INC, 2020)
PURPOSE: To compare the efficacy and safety of accelerated corneal cross-linking (CXL) with conventional CXL in pediatric patients with keratoconus. METHODS: Consecutive patients with keratoconus received either accelerated CXL (9 mW/cm(2) irradiance for 10 minutes) or conventional CXL (3 mW/cm(2) irradiance) for 30 minutes. Visual acuities (uncorrected [UDVA] and corrected [CDVA] distance visual acuity, logMAR), spherical error, cylindrical error, spherical equivalent, and keratometric values were recorded. Followup measurements were compared with baseline values. RESULTS: The study enrolled 48 eyes: 22 eyes had accelerated CXL (mean age: 16.0 +/- 1.7 years) and 26 eyes had conventional CXL (mean age: 15.7 +/- 1.6 years). Compared with preoperative values, all mean keratometric values significantly improved in the accelerated CXL group (flat [K1]: Delta = -0.64 D, P < .0001, steep [K2]: Delta = -0.63 D, P = .009 and Kmax: Delta = -0.55 D, P = .028), but no significant changes were observed in the mean UDVA and CDVA. In the conventional CXL group, all mean keratometric values and CDVA significantly improved (K1: Delta = -0.65 D, P = .017, K2: Delta = -0.87 D, P = .006, Kmax: Delta = -1.47 D, P = .011). No significant changes were observed in refractive error in either CXL group. There were no significant differences in the keratometric readings, visual acuities, or refractive error between the two groups at the 2-year follow-up. CONCLUSIONS: Both conventional and accelerated CXL protocols appear to be effective in stabilizing keratoconus progression in pediatric patients. Improved CDVA was also observed in the conventional CXL group. Accelerated CXL, with its advantage of shorter treatment duration, may be an alternative in pediatric patients.
Keywords: PROGRESSIVE KERATOCONUS; RIBOFLAVIN; CHILDREN; AGE